Indigenous Knowledge Degradation of Lom community, Bangka Island in identifying and using Pelawan Padang (Tristaniopsis merguensis) - Hartanto, Salpa; Sulistyaningsih, Yohana C; Walujo, Eko Baroto (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Pelawan padang (Tristaniopsis merguensis) plays an important role in providing daily needs including goods and services for Lom community in Bangka island. Recently, modernization has an impact on the indigenous knowledge related to plants utilization in Lom community, especially pelawan padang. The aims of the study were to analyze the roles and benefits and to determine ethnobotanical knowledge changes of Lom people on the use of pelawan padang. Data were collected through interviews using a structured questionnaire. Pebble Distribution Method (PDM) was used to analyze the quantitative data, while the qualitative data were analyzed using descriptive statistic. The result showed that pelawan padang can be used for material construction, firewood, honey production, traditional medicine and material of bagan traditional stilt houses. The degradation of indigenous knowledge of Lom people related to natural resources such as pelawan padang could be assessed according to individual factors which were; age classes and occupation. More respondents aged over 40 years showed the ability in identifying and using Pelawan padang compared to the younger (25-40 years old). According to occupational group, there was higher number of unemployed respondents and respondents working as farmers that used pelawan padang compared to respondents working as employee. No difference was found for tribal leaders and community members regarding to the knowledge of Pelawan padang benefits. This study provides the latest information about the benefits of plants from the Lom Community that can be developed through the further research, especially for the benefits pelawan padang as a drug.